Glaucoma in Saudi Arabia: A Challenging Public Health Concern – A Narrative Review: Doi: 10.36351/pjo.v39i3.1643 - Alluwimi, Muhammed S. (Pakistan Journal of Ophthalmology, 2023)
The aim of this narrative review is to investigate and summarize studies conducted for prevalence of glaucoma in Saudi Arabia. Search criteria were; published studies after theyear of 2000 and included Saudi population. Any studies that focused on subtypes of glaucoma and their relations with other ocular conditions were excluded. There were three studies that estimated the prevalence of glaucoma in Saudi Arabia. The prevalence reported in these studies ranged from 5.4% to 5.8%. However, these studies were conducted in specific regions and did not represent the national prevalence of glaucoma in Saudi Arabia. It was concludedthat there is a high demand for accurate estimate for the national prevalence of glaucoma in Saudi Arabia. Accurate estimate of prevalence and epidemiology of glaucoma leads to constrain the challenges of glaucoma as a public health concern in Saudi Arabia.